Apgar score and hospitalization for epilepsy in childhood: a registry-based cohort study - Pedersen Lars; Sørensen Henrik T; Ehrenstein Vera; Larsen Helle; Holsteen Vibeke; Rothman Kenneth J (BMC, 2006)
Abstract Background A depressed Apgar score at 5 minutes is a marker for perinatal insults, including neurologic damage. We examined the association between 5-minute Apgar score and the risk of epilepsy hospitalization in childhood. Methods Using records linked from population registries, we conducted a cohort study among singleton children born alive in the period 1978-2001 in North Jutland County, Denmark. The first hospital discharge diagnosis of epilepsy during the follow-up time was the main outcome. We followed each child for up to 12 years, calculated absolute risks and risk differences, and used a Poisson regression model to estimate risk ratios for epilepsy hospitalization. We adjusted risk ratio estimates for birth weight, gestational age, mode of delivery, birth presentation, mother's age at delivery, and birth defects. Results One percent of the 131,853 eligible newborns had a 5-minute Apgar score <7. These children were more likely to be hospitalized with epilepsy during the follow-up than were children with an Apgar score of 7 or greater. The crude risk difference for epilepsy hospitalization was 2.5 cases per 100 (95% confidence interval [CI] 1.3 to 3.8). The risk difference estimates were greater in the presence of other perinatal risk factors. The adjusted risk ratio was 2.4 (95% CI 1.5 to 3.8). Half of the 12-year risk for epilepsy hospitalization in those with a depressed Apgar score occurred during the first year of life. The risk ratio during the first year of life was 4.9 (95% CI 2.0 to 12.3). Conclusion An Apgar score <7 at five minutes predicts an increase in the subsequent risk of epilepsy hospitalization. This association is amplified by other perinatal risk factors.